Successful Living Donor Kidney Transplantation in 72-Years-Old Women with Diabetes Mellitus: Beyond the Age of Life Expectancy In Myanmar! - Pyar, Khin Phyu; Hla, Sai Aik; Shwe, Win Kyaw; Aung, Zarni Htet; Myint, Thein Tun; Win, Thurein; Kyaw, Aung Phyoe; Htet, Aung Zaw; Lwin, Kyaw Thu Yein; Maung, Lay Maung; Hein, Ye Min; Maung, Myo Maung; et al. (Jour Med Resh and Health Sci, 2023)
The average life expectancy in Myanmar is 66.8 years according to WHO (2020). We presented two cases of successful living kidney transplant in 72 years and 73 years old women; they had maintenance hemodialysis for 3 months and 2 years respectively for end stage renal disease (ESRD) due to long standing diabetes mellitus. The upper limit of age of recipient for living donor kidney transplant was discussed. Age per se should not represent a barrier to transplantation.